Critical energy distribution and fracture characteristics of heterogeneous rock under splitting condition - Hongguang JI; Zhen FU; Yuezheng ZHANG; Chunrui ZHANG; Dongsheng CHEN (Meitan xuebao)
To explore the macroscopic physical and mechanical characteristics of the tensile fracturing of heterogeneous rocks under loading, uniaxial splitting tests were designed and carried out on rock samples. By collecting rock deformation characteristics, acoustic emission parameters, and surface temperature field characteristics, the study analyzed and revealed the deformation coordination, critical energy distribution, fracture characteristics, and critical characteristics under local stress stages in the rock splitting process. Through quantitative calculation, the study obtained the spatial variability characteristics of the deformation of granite. It also conducted relevant analyses on the acoustic emission bi value, critical energy distribution, RA (rise time/amplitude) - AF (average frequency) characteristic parameters, and fracture surface morphology of granites with different deformation coordination during the loading process. The experimental results show: ① The deformation space variability coefficient at the 90% peak stress level of the rock can be used to evaluate the differences in rock deformation coordination, and it is approximately negatively correlated with the tensile strength of the specimen; ② The acoustic emission bi value shows a “fluctuating-rising-falling” trend during the loading process. Samples with different deformation coordination have different proportions of acoustic emission events at different stress levels, and the more coordinated the deformation, the more stable the growth pattern of acoustic emission events; ③ The splitting and fracturing process of granites with different deformation coordination exhibits self-organized critical characteristics. The energy probability density functions of the entire process and the local stress stages follow power-law distributions, and as the deformation coordination deteriorates, the power-law distribution curve in the local stress stage at the later stage of loading gradually approaches the power-law curve of the entire process; ④ The change patterns of RA - AF values are similar for samples with different deformation coordination, but the samples with poorer deformation coordination have lower tensile strength, larger deformation space variability, more small-scale tensile fractures, rougher fracture surfaces with larger JRC, smaller released energy, and are more likely to enter a critical state, while the opposite is true for rocks with better deformation coordination. Based on the above research, it is shown that the multi-point strain pattern of the surrounding rock of the deep tunnel can be monitored in real time, and the points with a sudden increase in the coefficient of variation of the deformation space can be used as the early warning information for the tensioning and rupture of the tunnel.